Thematic Teaching Materials of Connected Type Sultan Mahmud Badaruddin I Palembang Mosque Materials Mathematics for Class II Elementary School - Syaifudin Syaifudin; Bonita Hirza; Luvi Antari; Amrina Rizta; Rohman Rohman (STAI Hubbulwathan Duri, 2024)
Connected type teaching materials are part of thematic learning which can be used as an alternative in facilitating mathematics learning. The material chosen is math material in grade II elementary school including multiplication, division, and simple plane shapes. The theme used in this study is the Great Mosque of Sultan Mahmud Badaruddin I Palembang which is well known to students. This research is a development research using the stages of development of Tessmer and Akker. The two major stages of this development research are: (1) Introduction, and (2) Formative Evaluation. Data collection with walkthroughs, documentation and tests. Data analysis was in the form of product analysis of teaching materials by looking at the results of tracing and documentation of the one to one stage, expert reviews and small groups, and analysis of test data obtained from the field test stage. Based on the results of product analysis, valid and practical teaching materials were obtained. Validity can be seen from the results of the assessment of content/content experts (according to the thematic approach of the connected type), construct experts (according to the characteristics of teaching materials), and language experts (according to PEUBI). Practically seen from the results of students' assessments in small group trials where students stated that the teaching materials provided were easy to understand. The potential effect is seen from the evaluation test results. The teaching materials compiled were declared valid after going through the one to one stage, expert review which had been revised according to expert advice. Practically illustrated from the results of small groups that have gone through the revision stage. The potential effect of this study is 86.1 and is included in the very good category.